Analyzing an "Off-Ladder" allele at DXS10135 from the AGCU X19 STR kit. (December 2017) - Li, Jienan; Deng, Chuncao; Luo, Haibo; Song, Feng; Hou, Yiping
Abstract: X chromosome STRs (X-STRs) have been proven to be an important tool for some complex kinship analyses in recent years. A novel 19 X-STRs multiplex system named as AGCU X19 STR Kit was developed and widely used for population genetics as well as forensic case works. In this study an "Off-ladder" allele between allele 21 and allele 21.1 at DXS10135 has been observed in AGCU X19 STR Kit. The "Off-ladder" allele was about 0.4 bases longer than the allele 21 of allelic ladder of DXS10135 in AGCU X19 STR Kit. To avoid DNA profile misunderstanding or mislabeling, "Off-ladder" allele at DXS10135 was analyzed by sequencing and detected with Investigator Argus X-12 Kit, respectively. Our results showed this "Off-ladder" allele was allele 21 at DXS10135. It was caused by inaccurate allele 21 of allelic ladder of DXS10135 in AGCU X19 STR Kit.